Interaction between Pluronic F127 and Dioctadecyldimethylammonium Bromide (DODAB) Vesicles Studied by Differential Scanning Calorimetry - Feitosa, Eloi [UNESP]; Winnik, Francoise M. (Amer Chemical Soc, 2010)
A number of fundamental studies on the interactions between lipid bilayers and (ethylene oxide)-b-(propylene oxide)-b-(ethylene oxide) copolymers (PEO-PPO-PEO, Pluronics) have been carried out recently as model systems for the complex behavior of cell membranes with this class of polymers often employed in pharmaceutical formulations. We report here a study by differential scanning calorimetry (DSC) of the interactions in water between Pluronic F127 (F127), and the cationic vesicles of di-n-octadecyldimethylammonium bromide (DODAB), as a function of concentration of the two components (DODAB 0.1 and 1.0 mM; F127 0.1 to 5.0 mM) and of the sample preparation protocol. The DSC studies follow the critical micellization temperature (cmt approximate to 27 degrees C at 1.0 mM) of F127 and the gel-liquid crystal transition (T(m) approximate to 45 degrees C) of the DODAB bilayer and of F127/DODAB mixtures. Upon heating past T(m) vesicle/polymer mixtures undergo an irreversible conversion into mixed DODAB/F127 micelles and/or F127-bearing vesicles, depending on the relative amount of each component, together with, in some cases, residual intact F127 micelles or DODAB vesicles. Sample preparation protocol is shown to have little impact on the composition of mixed systems once they are heated above T(m).